The mid-oceanic ridges mountains below sea level - Nicolas, Adolphe 1936-2020 (Springer, 1995)
Despite turbulent actions of plate tectonics, continents, which since the first cooling of the planet float on its substratum, are a geological record of the history of Earth. Since the existing oceans are geologically relatively young, they register the activity, the life of the Earth. They formed when a large supercontinent (Pangea) broke apart some 150 Ma ago. The mid-oceanic ridges are narrow belts of submarine mountains marking the boundaries between plates which are moving apart, with new oceanic crust being created at the same time. Under the continents oceanic crust is subducted. The ocean bottom is an ideal location to study recent geodynamic processes on Earth. Of special interest to the reader will be the combination of the most recent oceanographic data with ophiolites, representing fossil ocean crust, obducted onto the continents by tectonic processes.
Dt. Ausg. u.d.T.: Nicolas, Adolphe: Die ozeanischen Rücken
Keywords: Geomorfologia marinha; Mid-ocean ridges; Sea-floor spreading; Ozeanischer Rücken; Magmatisches Gestein; Plattentektonik; Mittelozeanischer Rücken